PERSEPSI MAHASISWA TERHADAP KINERJA DOSEN BERDASARKAN PERBEDAAN GENDER PADA PROGRAM DIPLOMA TIGA STIESIA SURABAYA - Nur Handayani (EKUITAS (Jurnal Ekonomi dan Keuangan), 2006)
This research is conducted in the purpose to prove an empirical evidence of the gender differences between male and female lecturers’perfomance in Program Diploma Tiga STIESIA Surabaya. Sample is taken by stratified random sampling, samples are 65 respondent measuring the performance of male lecturers and 70 respondent measuring the performance of female lecturers from 364 students in Program Diploma Tiga STIESIA Surabaya at academic sesion 2005/2006. The lecturer’s performance survey model developed by Green et.al (1998) was use for this research. The result of t-test proves that the performance between male and female lecturers in Program Diploma Tiga STIESIA Surabaya is not significant.